Corporate governance and corporate profitability: Evidence from Sri Lanka. - Anandasayanan, S. (University of Jaffna, 2024)
The poor performance of commercial organizations is frequently attributed to the absence of effective corporate governance. Developed economies with a strong private sector and well-established corporate governance systems consistently post high and steady growth rates. The main purpose of this study is to explore the effect of corporate governance mechanisms on a firm's Return of listed companies in CSE. Data collection was carried out on the 208 companies during the period 2015 to 2020. Size of the board, Board composition, Chief Executive Duality, and Institutional ownership were taken as the explanatory measures and ROA was taken as a proxy of corporate profitability. Furthermore, firm size, and firm age and Debt to Equity Ratio were taken as control measures. To explore the effect of governance mechanisms on a firm's Return, panel data regression was applied. According to the results of the panel data analysis, Board size, Board composition, and firm size have a significant impact on the profitability of the listed companies in Sri Lanka. Moreover, institutional ownership and CEO duality have no impact on Return on Assets. In the normality test, the p-value of the Jarque–Bera value for all models is found to be greater than 0.05. This satisfies the point that the residual has the normality. The findings of this research are vital for policy implications in Sri Lanka.
Keywords: Corporate Governance; Corporate Profitability; Debt to Equity; Board size; Board composition; CEO duality